(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
World sugar consumption has been recording a steady growth in the past 70 years and, according to all relevant estimates, it will continue to grow also in the next decade, which puts sugar in the category of the most significant foods and commodities in the world. Of the total world sugar production, around 77% is derived from sugar cane and 23% from sugar beet. Brazil has been the world leader in sugar production for a long period of time, producing white sugar from sugar cane only, whereas the leader in the production of sugar derived from sugar beet is the EU-28. When the Republic of Croatia joined the EU, the Croatian sugar industry became part of the single European sugar market, so the break-even point was used in the research to determine the competitiveness level of the Croatian sugar beet production. Based on the expected selling price of sugar beet amounting to EUR 34 per ton of standard quality sugar beet, and using the break-even method, it was determined that the quantity required to cover total costs in sugar beet production in the Republic of Croatia amounts to 55.26 tons per hectare of payable sugar beet, standard quality, i.e. 8.84 tons of polarized sugar per hectare. As the average sugar beet production in the Republic of Croatia, expressed in the equivalent of polarized sugar, amounts to 7.8 tons per hectare, it is obvious that an average Croatian producer of sugar beet, without income from subsidies, operates at a loss.